(3TQM eHMK GdGSJUMGH ef aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3hEPG YQaJ gPjf GdebOeJjf afbhd aQV GdNUe chf GSJUMGH YOe GdQGaY MGce Ydi GSJUMGH YOe GdSHHjI hYOe GdJCKjQ dG eYfi dg MjK Efg ebJVi chfg MGceGs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg cGf Mceg Cj Mce MOhK GdMGOK GdeQGO GSJUMGH YOeg, bhdg Mce CMO GdMGOKjf ef LgI GdYde GdGLeGdj HCfg CeG MOK bHd gPG GdMGOK GdBNQ hCeG HYOgs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs